Happiness: Psikologi Positif Versus Psikologi Islam - Hamdan, Stephani Raihana (Unisia, 2018)
In recent study, psychology started to focus not only about mental disorders but also focus on new themes, such as happiness. To make a strong family bond, happiness is an essential. Reseacher try to analyze the concept of happiness in two new waves of psychology, which is positive psychology and Islamic psychology. Positive psychology use term of well being to explain and measured happiness. Islamic psychology has different perspective about happiness, that makes definition about happiness in Islamic term could not use well-being to measure happiness. The two waves also different in term of determinant, indicators and how to increase happiness.Hopefully this article could be a basic foundation to develop new set of concept and measurement of happiness with eternal happiness paradigm.